The Importance of Inculcating Character Education in Facing the Era of Globalization in the 21st Century Generation - Aulia Khumairoh (LPPM Universitas Negeri Yogyakarta, 2022)
Character education is an education system that aims to instill character values in individuals in which there are components of knowledge and awareness in acting. Character education is closely related to moral education where moral education also aims to shape and train individual abilities in realizing good ways of thinking and behaving. Character education aims to develop essential potential in humans where in the future they can become clever individuals in regulating all their actions and differentiating good and bad. Character education is an effort to form an honest, caring and loving character for the homeland. Character is a characteristic of each different individual. In humans, The formation of this character requires coaching to form a good character in order to become a generation that has advanced thinking. Developments in the 21st century have brought many changes, based on these problems, this study seeks to analyze efforts to instill character values in individuals, especially for the 21st century generation.The research method used is a literature review method from 20 sources in the form of journal articles and websites using a quantitative deductive approach by analyzing the data used in accordance with the themes discussed.the res b ults of this study finds how the effect of changes in the cultivation of character education due to the Covid 19 outbreak that occurred in the 21st century and how to use other information media as a means of planting.